Induction of osteogenic differentiation in a rat calvarial bone defect model using an In situ forming graphene oxide incorporated glycol chitosan/oxidized hyaluronic acid injectable hydrogel. (30th October 2020) - Lee, Sang Jin; Nah, Haram; Heo, Dong Nyoung; Kim, Kyoung-Hwa; Seok, Ji Min; Heo, Min; Moon, Ho-Jin; Lee, Donghyun; Lee, Jae Seo; An, Seong Yeong; Hwang, Yu-Shik; Ko, Wan-Kyu; et al.
Abstract: Graphene oxide (GO) incorporated hydrogels have received great attention and have shown excellent potential for use in the field of bone tissue engineering due to their unique osteogenic functionalities. However, current hydrogel systems are limited in their ability to provide an appropriate amount of GO to the lesion area. To overcome this issue, we designed a GO incorporated glycol chitosan (gC)-hyaluronic acid (HA) injectable hydrogel system via a simple oxidation technique. Through oxidation, aldehyde groups were introduced onto the HA. Blending this with gC allowed for the formation of an aqueous hydrogel matrix. Physico-chemical characterization demonstrated that the gC/oHA/GO hydrogel matrix exhibited robust mechanical properties and stability. The in vitro and in vivo results showed that GO incorporated injectable hydrogels enhanced bone tissue regeneration as compared to control injectable hydrogels. Therefore, our results indicate that our injectable hydrogel system could be used for delivering GO. This material may serve as an excellent tissue scaffold for use in treating bone defects. Graphical abstract: Image 1 Highlights: Through oxidation process, aldehyde groups introduced onto the pure hyaluronic acid. The developed injectable hydrogel could easily modulate the graphene oxide content. The biological results showed that graphene oxide incorporated injectable hydrogels enhanced bone tissue formation both in vitro and in vivo.